17 TH ASEAN ministerial meeting and post-ministerial meeting with the dialogue countries. Jakarta, 9-12 July 1984 - MEETING AND POST-MINISTERIAL MEETING WITH THE DIALOGUE COUNTRIES (1984 : Jakarta) (1984)
116 hlm ilus 29 cm